2013
DOI: 10.1002/humu.22262
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risks forMLH1andMSH2Mutation Carriers

Abstract: We studied 17,576 members of 166 MLH1 and 224 MSH2 mutation-carrying families from the Colon Cancer Family Registry. Average cumulative risks of colorectal cancer (CRC), endometrial cancer (EC) and other cancers for carriers were estimated using modified segregation analysis conditioned on ascertainment criteria. Heterogeneity in risks was investigated using a polygenic risk modifier. Average CRC cumulative risks to age 70 years (95% confidence intervals) for MLH1 and MSH2 mutation carriers, respectively, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
131
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 211 publications
(138 citation statements)
references
References 42 publications
7
131
0
Order By: Relevance
“…Of the 12 studies that did quantify the risk, six of these reported a statistically significant increase in prostate cancer for Lynch syndrome (19,27,32,33,35,36). The remaining six studies found no evidence for an increased risk of prostate cancer (14,15,(22)(23)(24)34). Three studies estimated prostate cancer risk using retrospective cohort of family members including relatives of confirmed carriers who were not tested themselves for a germline mutation (24,27,35).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 12 studies that did quantify the risk, six of these reported a statistically significant increase in prostate cancer for Lynch syndrome (19,27,32,33,35,36). The remaining six studies found no evidence for an increased risk of prostate cancer (14,15,(22)(23)(24)34). Three studies estimated prostate cancer risk using retrospective cohort of family members including relatives of confirmed carriers who were not tested themselves for a germline mutation (24,27,35).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies estimated prostate cancer risk using retrospective cohort of family members including relatives of confirmed carriers who were not tested themselves for a germline mutation (24,27,35). Eight retrospective cohort studies estimated prostate cancer risk only for mutation carriers using population-based resources (22) or clinic-based resources (19,24,32,(34)(35)(36) or both population-and clinic-based resources (15). Only one study estimated risk using a prospective cohort design; estimating prostate cancer risk for carriers without a prior diagnosis of any cancer (14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 There is published evidence suggesting that performing a WCR analysis would not change the results significantly. A major argument for not performing a WCR was given in a recent publication by the Jenkins research group, 5 where they report that evidence of CRC and endometrial cancer (EC) risk being dependent on setting (clinic vs. population) was weak or absent due to the fact that there was no difference observed between clinic-and population-based families for either CRC or EC risk. This is supported by the unweighted and weighted analysis reported by Pande et al, 6 where there is no or very little difference in the observed hazard ratio (HR) between the unweighted and WCR when testing ascertainment source-clinic.…”
Section: Dear Editormentioning
confidence: 99%